Undergraduates garnered 6 gold medals and three special awards at i-ENVEX - Abdul Rahman, Ahmad
Universiti Malaysia Pahang (UMP) undergraduates won six gold medals, three silver medals and six bronze medals at the International Innovation and Engineering Exhibition (i-ENVEX) on April 19, 2013 at Arau, Perlis.